2022
DOI: 10.1038/s41598-022-18717-4
|View full text |Cite
|
Sign up to set email alerts
|

Application of growth promoting hormones alters the composition and antioxidant potential of dill essential oil under salt stress

Abstract: The performance of dill plant may be affected by adverse environments such as salinity. Thus, this research was designed to evaluate changes in chemical composition and antioxidant activity of seed essential oil of dill (Anethum graveolens L.) in response to salinity (0, 5, 10 and 15 dS/m) and 1 mM of each hormonal treatments (gibberellic acid, salicylic acid, and cytokinin). Salicylic acid (SA) reduced Na+ content of roots and leaves by 15.4%, 30.9% and 12.4%, 24.3%, but enhanced K+ content by 29.8%, 51.6% an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 57 publications
(59 reference statements)
2
9
1
Order By: Relevance
“…In the present study, positive relationships were also observed between IC 50 and TPC under drought conditions. Compared to our finding, previous studies indicated a significant correlation between antioxidant activity and TPC in C. cyminum 13 and C. sativum 34 .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In the present study, positive relationships were also observed between IC 50 and TPC under drought conditions. Compared to our finding, previous studies indicated a significant correlation between antioxidant activity and TPC in C. cyminum 13 and C. sativum 34 .…”
Section: Discussioncontrasting
confidence: 99%
“…Similarly, the phenolic contents of cumin under water stress increased greatly 13 . In contrast, Neffati et al 34 reported that the polyphenol content decreased under salinity stress in coriander (C. sativum L). The different trends in phenolic fractions under drought stress can be imputed to the synthesis of various components of TPC and TFC as efforts by various populations to adapt to different soil moisture levels.…”
Section: Discussionmentioning
confidence: 88%
“…The quantity and quality of essential oils in medicinal plants can be influenced by environmental stresses and nutrient availability. Despite a reduction in plant productivity, different results have been reported on the variation of secondary metabolites of medicinal plants in response to salinity levels 28 , 30 , 31 . Increasing essential oil content at high level of salinity (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, variations of essential oil components are affected by changes in physiological functioning of plants and the induction of the specific enzymes involved in the biosynthesis of these compounds by salinity [37][38][39] . In response to salt stress, plants adapt through a number of mechanisms, such as salicylic acid (SA) signaling 28,29,35 . Salicylic acid is an efficient stimulant for secondary metabolite production that involves in the synthesis of terpenoids 40 .…”
Section: Bnc-feo + Bnc-znomentioning
confidence: 99%
See 1 more Smart Citation